1994
DOI: 10.1093/jnci/86.17.1286
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Apoptosis: Integration of Genetic, Biochemical, and Cellular Indicators

Abstract: Apoptosis, or programmed cell death, is defined by morphologic change resulting in nonpathologic cell loss and is relevant to a wide spectrum of biology. The process is best characterized in the nematode Caenorhabditis elegans where ced genes mediate the death of specific cells during development. Some corresponding genes have been identified in mammalian cells. Expression of the mammalian bcl-2 gene (homologous to ced-9) suppresses apoptosis in many systems. The ced-3 gene is homologous to a mammalian proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
129
0
9

Year Published

1996
1996
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(140 citation statements)
references
References 0 publications
2
129
0
9
Order By: Relevance
“…Some authors have suggested that CCB may have a negative influence on apoptosis, programmed cell death, which has been under investigation regarding its role in oncogenesis [26]. Transmembrane calcium signals influence and cause cell differentiation and apoptosis [27,28].…”
Section: Antihypertensivesmentioning
confidence: 99%
“…Some authors have suggested that CCB may have a negative influence on apoptosis, programmed cell death, which has been under investigation regarding its role in oncogenesis [26]. Transmembrane calcium signals influence and cause cell differentiation and apoptosis [27,28].…”
Section: Antihypertensivesmentioning
confidence: 99%
“…[1][2][3] Apoptosis typically occurs in single cells, eventually eliminated by phagocytosis 4 in the absence of an inflammatory reaction. One of the most characteristic events of apoptosis is the internucleosomal fragmentation of nuclear DNA, 5 which might be revealed either by Southern blotting techniques, which show a characteristic ladder pattern caused by the migration of DNA fragments corresponding to nucleosomes or multiples of nucleosomes, 6 or by in situ techniques of end labeling the nuclear DNA fragments, 7 such as the TUNEL 8 or other ISEL 9,10 assays.…”
Section: Copyright 1997 By the American Association For The Study Of mentioning
confidence: 99%
“…Described as a counterpart of mitosis, transgene has been described by this laboratory. Several apoptosis has been the focus of a large number of studcell lines have been established from the livers of two of ies since it was first described by Kerr et al [1][2][3][4][5][6] Affecting these rats. One of these cell lines, L37, exhibits a large single or small groups of cells, apoptosis exhibits nuclear/cytoplasmic ratio and a well-differentiated cyto-changes in cellular ultrastructure that are distinct plasm containing numerous organelles.…”
mentioning
confidence: 99%